2017
DOI: 10.1308/rcsann.2017.0001
|View full text |Cite
|
Sign up to set email alerts
|

Current practice of antibiotic prophylaxis during elective laparoscopic cholecystectomy

Abstract: INTRODUCTION Current guidelines do not recommend antibiotic prophylaxis in elective laparoscopic cholecystectomy. Despite this, there is wide variation in antibiotic prophylaxis during cholecystectomy in population-based studies. The aim of this survey was to establish the current rationale for antibiotic prophylaxis in elective laparoscopic cholecystectomy. METHODS A short questionnaire was designed and disseminated across collaborators for a population-based study investigating outcomes following cholecystec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, the unnecessary use of antibiotics is commonplace. A study showed that 94.5% of professionals used ABP in elective LCs 15 . In our study, about a quarter of the evaluated patients received ABP, despite having no risk factors that justified this approach.…”
Section: Discussionmentioning
confidence: 99%
“…However, the unnecessary use of antibiotics is commonplace. A study showed that 94.5% of professionals used ABP in elective LCs 15 . In our study, about a quarter of the evaluated patients received ABP, despite having no risk factors that justified this approach.…”
Section: Discussionmentioning
confidence: 99%
“…No statistical difference (p-value=0.915656) was observed among the groups in deep and superficial infections. 18 Laparoscopic cholecystectomy, has evolved in technique, instrumentation and postoperative management yet there is a wide variation in the management, especially in antibiotic prophylaxis during cholecystectomy. Studies have failed to demonstrate any clinical benefit, such as reduction in surgical site infections in patients administered antibiotic prophylaxis during an elective cholecystectomy.…”
Section: A Total Of 135 Patients Underwent Lc In the Study Period;mentioning
confidence: 99%
“…Antibiotic prophylaxis plays an important role in the prevention of wound infections. [ 10 11 ] The prevention of PSI is arguably a better approach than management, once infection has developed, which can prove to be frustrating both for the patient and the operating surgeon. [ 10 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…These are given at the induction of general anesthesia. [ 10 11 ] Topical antibiotics are applied to postoperative wounds as these may prevent surgical site infection. Several benefits of using antibiotics topically rather than systemically have been documented.…”
Section: Introductionmentioning
confidence: 99%